Analisis keakuratan verifikasi dosis dengan menggunakan perbandingan phantom standar dan phantom replika - Ardian Handoko; Hidayatullah Hidayatullah; Eko Hidayanto; Very Richardina (Youngster Physics Journal, 2018)
In the medical and radiology, phantom used as a simulator for the human body for radiotherapy activities. Most of them use homogeneous or standard phantom that have density same as water. This research was done because in real case, in the human body not only consists of soft tissue, but also there are other tissues such as lung and bone. By measuring using a non-homogeneous phantom or replica phantom with different materials densities, we compared the dose accuracy results from planning by this two phantom types. Replica phantom uses materials such as pine wood instead of lungs, polypropylene as a substitute for fat, acrylic instead of cartilage and solid silicon can change the bone. The study was conducted by varying the standard field area i.e., 3x3 cm, 5x5 cm, 10x10 cm, 15x15 cm, 20x20 cm and the mix area field. Obtained accurate results in standard phantom, i.e., 95.2%, 86.7%, 94.3%, 94.8%, 93.1% and 97.3%. Then on replica phantom accuracy is 94.7%, 95.6%, 96.2%, 86.0%, 91.6% and 96.6%. Keywords: Treatment planning system (TPS), Dose, Standard phantom, Non-homogeneous phantom, Replica phantom, Non-homogeneous tissue